Production competitiveness on regional food markets of Ukraine (Mongolian Journal of Agricultural Sciences, 2015)
Competitiveness is the main driving force to the stable prosperity of a country and the increase of its citizens’ welfare. Agriculture is an important part of the economy of any country. The processing industries are a powerful driving force for rural development. The necessary prerequisite to ensure food security of any country is the successful development of the food market. In Ukraine approximately 10 thousand companies are involved in the food production. The food industry is among the leaders in terms of foreign direct investment into the industry of Ukraine. Transnational corporations are actively operating in the field of food production in Ukraine. The agro-industrial complex in general and food industry in particular can guarantee a significant increase in GDP of a country and as a result improve its position in the world markets.Journal of agricultural sciences №15 (02): 166-172, 2015